Investigating Students’ Motivation through Game-Based Learning in Listening Classroom - Amanda, Nabila Ayu; Hadi, Meilda Mustafidah; Aulia, Nurhalisa Afti; Putri Hidayat, Regina; Hidayat , Didin Nuruddin; Mulyati, Yatni Fatwa (Universitas Sarjanawiyata Tamansiswa, 2024)
Most students feel that listening is a difficult English skill because the strategies that the teachers use in listening classes are too monotonous, so students feel unmotivated in the learning process. However, there is a lack of researchers who have studied the implementation of running dictation games to increase students' motivation. This research aims to examine the use of games, especially running dictation games, in increasing student motivation in listening classes. This research was conducted at Mts. Darunnaim YAPIA, involving 23 students from 7th grade. The researcher used a qualitative approach to compile this research. The data was collected through the questionnaire for all of the 7th-grade students, and the Interviews with several students after the game was implemented. This study also analyzed the data with descriptive analysis and thematic analysis. The results of this research show that the motivation of Grade 7 YAPIA students still needs to improve due to external factors such as the strategies used, and media that does not support learning. In addition, the use of running dictation games in the learning process can boost students motivation and enhance their participation in the listening classroom